Plane Viscous Flow Through the system of Moving Rods - Zachara, A. (Engineering Transactions, 1984)
The subject of this paper is a steady flow of an incompressible fluid about the system of two parallel rows of cylindrical rods, moving along their axes. The row of cylinders has been considered as a continuous surface, which allowed for the nonzero normal as well as the tangent velocity component. Both surfaces have been treated as moving walls of a parallel channel. The inner and outer flows have been calculated with the aid of perturbation methods applied to suitable exact solutions of the Navier-Stokes equations. Both solutions have been matched with the use of proper conditions at the wall to obtain a continuous flow description in the whole region. Pressure, velocity and streamlines distributions have been calculated. The error of the adopted approximation has been estimated and discussed.